2021
DOI: 10.1186/s12955-021-01703-1
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression are risk factors for recurrent pregnancy loss: a nested case–control study

Abstract: Background To evaluate the interaction of depression and anxiety with the development of recurrent pregnancy loss (RPL). Methods A nested case–control study involving 2558 participants was conducted with data from the prospective Miscarriage Woman Cohort study between 2017 and 2019 in the province of Gansu, China. The questionnaire data, self-rating anxiety scale and self-rating depression scale were collected after each participant’s first miscarr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Depression, anxiety, and stress symptoms were positively correlated with RPL, and their mean scores were significantly higher among women with confirmed RPL. The results of this study were reminiscent of the finding of Wang et al (2021), which reported a higher prevalence of depression and anxiety among women with RPL [ 47 ], suggesting that existing symptoms of depression and anxiety are contributors to the increased risk of RPL. A similar outcome was reported in studies on Chinese [ 48 ], Danish [ 49 ], and Iranian [ 50 ] populations.…”
Section: Discussionsupporting
confidence: 82%
“…Depression, anxiety, and stress symptoms were positively correlated with RPL, and their mean scores were significantly higher among women with confirmed RPL. The results of this study were reminiscent of the finding of Wang et al (2021), which reported a higher prevalence of depression and anxiety among women with RPL [ 47 ], suggesting that existing symptoms of depression and anxiety are contributors to the increased risk of RPL. A similar outcome was reported in studies on Chinese [ 48 ], Danish [ 49 ], and Iranian [ 50 ] populations.…”
Section: Discussionsupporting
confidence: 82%
“…The anxiety level of pregnant women who experienced one miscarriage was markedly elevated until the week of gestation of the prior pregnancy loss and then decreased after passing this critical window of time, while the anxiety level of RPL pregnant women continued to increase (Ridaura and Raich, 2017). Either depression or anxiety alone could increase the risk of subsequent RPL, and they had a synergistic effect after the first miscarriage which increased the development of subsequent RPL disease (Wang et al, 2021). Most previous studies on psychological adjustments in RPL women had relatively small sample sizes, and sociological factors and maternal history factors are not combined.…”
Section: Discussionmentioning
confidence: 99%
“…An article of previous miscarriage-related literature shows that almost half the women had features of depression disorder after pregnancy loss (Kulathilaka et al, 2016). Repetitious miscarriages cause women to suffer from both psychological and physical stress, which in turn increases the risk of subsequent miscarriage (Wang et al, 2021). Anxiety and depression were highly prevalent in pregnant women with a history of recurrent miscarriage, especially in early pregnancy, and then decreased (Qu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Whereas 9 months after the miscarriage, the data became 17%, 6%, and 18%, respectively. 32 A high incidence of anxiety (28.7%) and depression symptoms (48.6%) were found in recurrent pregnancy loss cases, 33 and 8.6% of the women met the criteria for moderate-to-severe depression. 34 In Guangzhou, China, the incidence rate of anxiety in early-stage, middle-stage and late-stage pregnancy was 47.6%, 36.1% and 32.5%, respectively, whereas the incidence of depression was 38%, 34.3% and 31.3%, respectively.…”
Section: Miscarriagementioning
confidence: 99%